Factors influencing consumer purchasing intention based on food labels - Zul Ariff Abdul Latiff; Nur Aisyah Ruslee; Mohamad Amizi Ayob (Canadian Research & Development Center of Sciences and Cultures, 2016)
This is a paper that highlighted on factors that influence the intention of consumers to buy food product based on food labels. Food label consist of any written, printed or graphic information that represent on the package of the product or is exhibited near the food for the purpose of promoting the sale or disposal. There are many factors contributing to the use of food labels on purchasing decision. Hence, the paper discusses on the factors influencing consumer purchasing intention based on food labels.